Family and Labour in Corfu Manufacturing, 1920–1944 - Kopanas, Dimitrios (The Historical Review/La Revue Historique, 2019)
This article concentrates on the relation between labour and family in the secondary sector of production of Corfu. It argues that family was crucial in forming the main characteristics of the labour force. The familial division of labour according to gender and age is examined not only as a decisive determinant in the categorisation of work positions as skilled and unskilled but also as a factor that defined the temporality or permanence of labour. It also focuses on the role of local and family networks and their effect on the labour market. These questions, thoroughly discussed by labour historians, will be applied to the case of Corfu, in an effort to complete the Greek paradigm.